Facilitators and barriers to engaging communities in health service research on dengue control in Indo-Pacific region: a systematic review - Cho Naing; Norah Htet Htet; Wong Siew Tung; Htar Htar Aung; Maxine A. Whittaker (BMC, 2023)
Abstract Background Dengue is a public health problem in the Indo-Pacific countries. There are concerns over the facilitators and barriers to community engagement in health service research aimed at dengue control. The objective of his study was to identify and synthesize facilitators and barriers to community engagement in health service research aimed at dengue control. Methodology The Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) checklist was used to perform this review. Health-related databases including PubMed, Ovid, and Google Scholar were searched for relevant studies. A consolidated framework with five domains was developed after undertaking a six-phase reflective thematic assessment of the data. Results Thirteen studies were identified, spanning eight low-and middle-income countries of the Indo-Pacific region including Cambodia, India, Indonesia, Myanmar, Philippines, Sri Lanka, Thailand, and Vietnam. The studies in this review covered the period from 2002 to 2021. A broad range of study designs and objectives were revealed across these 13 studies. An array of communities such as the local government, project-related health staff, local health services staff, community leaders, local communities/residences/general public, heads of households, community health volunteers, school teachers, and schoolchildren participated in these dengue related studies. The five Consolidated Framework for Implementation Research (CFIR) domains of 'intervention characteristics', 'inner setting', 'outer setting',' individual characteristics', and 'program implementations' were used to identify and describe barriers and facilitators. Conclusions The findings indicate a range of barriers and facilitators to community engagement in dengue control in the selected LMIC in the Indo-Pacific countries. Future health services research on dengue control approaches should be carefully planned, methodologically constructed, aligned with community engagement principles, and involve considerable community participation at all stages of the research.